RELEVANSI TEOLOGI REFORMASI BAGI PEMBENTUKAN KARAKTER KRISTEN DI ERA MODERN - Yusnita, Desy Milenia (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
This research examines the relevance of Reformation theology in the context of Christian character building in the modern era. Reformation theology, which prioritises the principles of Christianity based on the Bible, has contributed significantly to Christian identity and practice. In the face of pluralism and modernity, understanding and maintaining Christian identity is crucial. This research utilises an appropriate methodology to explore how Reformation theology remains relevant in shaping Christian character today. Calvin's teachings on God's sovereignty and predestination have shaped Christian character through an emphasis on humility, recognition of human limitations, and trust in God's plan. The Reformation also triggered social and cultural changes in favour of democracy, individual rights, and education. However, modern challenges such as secularism, moral and ethical changes, and the influence of technology and social media, are impacting Christian character formation by eroding Christian values, creating confusion, and influencing the younger generation. Nonetheless, these challenges also have the potential to strengthen Christian character and faith. This study confirms that the principles of Reformation theology such as Sola Scriptura, Sola Gratia, and Sola Fide, still make an important contribution in forming a solid Christian character. Amidst the challenges of the modern era, these principles must be understood and applied wisely by Christians to maintain the robustness of faith and relevance in Christian life. This research suggests that Reformation Theology can be a strong foundation in answering the challenges of Christian character building in an ever-changing age.